[un]gemalt. - Badovinac, Zdenka; Birnbaum, Daniel; Elkins, James; Essl, Agnes & Karlheinz; Gaensheimer, Susanne; Ginton, Ellen; Harrison, Charles; Humpl, Christine; Irwin; Kandl, Johanna; Koshyakov, Valery; Levin, Kim; et al. (Klosterneuburg (Wien) : Sammlung Essl Kunst der Gegenwart, 2002)
Anonymous ; IRWIN ; Kandl, Johanna ; Koshlyakov, Valery ; Nicolai, Olaf ; Pistoletto, Michelangelo ; Sonnenschein, Eliezer ; Dine, Jim ; Fontana, Lucio ; Francis, Sam ; Hartung, Hans ; Mathieu, Georges ; Prachensky, Markus ; Rainer, Arnulf ; Richter, Gerhard ; Rockenschaub, Gerwald ; Soulages, Pierre ; Stella, Frank ; Warhol, Andy
bibliog. p. 45, 59, 73, 87, 101, 115, 129
biog. p. 44, 58-59, 73, 86, 100, 114, 129
Duits & Engels
[un]gemalt, Sammlung Essl Kunst der Gegenwart, Klosterneuburg (Wien), 17.07. - 27.10.2002
boek